SEQUENCE STRATIGRAPHY OF LATE ALBIAN TO EARLY TURONIAN SUCCESSION IN THE DOMA LIJI STREAM WITHIN THE GOMBE INLIER, PART OF GONGOLA BASIN, UPPER BENUE TROUGH, NORTH EASTERN NIGERIA - M.I. Waziri; I. Hamidu; E.O. Obiosio; E.C. Nwaejije (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
A detailed geological fieldwork was carried out, and sections were logged. Three lithogenetic units were encountered within the Late Albian to Early Turonian succession in the Gombe Inlier. The Bima Group is about 60 meter thick and consists of brown colour, fine to coarse grained, pebbly trough cross bedded sandstone interbedded with thin clays. It overlies the basement unconformably, the Yolde Formation comprises of massive to bedded, dark grey to purple mottled clays and shales, the Fika Formation characterized by thin laminated shale, silty, fissile shale, oolitic iron stone with Thalassinoides and Skolithos burrows, and dark grey mudstone containing glauconite, gypsum bed and limestone nodules. The Yolde Formation in the Doma Liji stream shows a progradational to retrogradational stacking pattern within an overall transgressive systems tract, with the clinoform prograding into the sea while the shales above are retrograding land ward. The overall parasequences within the sequence of Yolde Formation in Doma Liji stream (clinoforms) were products of transgression that is caused when the rate of base – level rise outspaced the sedimentation rates at the coastline and normal regression that is caused when the rate of sediment supply outpaced the creation of accommodation space. The Yolde Formation in the Doma liji section is interpreted as comprising two parasequence sets (A and B). Set A is represented by thick tabular cross bedded, fine to medium grained sandstone at the base and grey coloured, medium grained trough cross bedded sandstone having a progradational parasequence stacking pattern. Set B represented by dark grey shale inter bedded with thin sandstone with thalassinoides burrows with a retrogradation stacking pattern. The maximum flooding surface is here interpreted to be the limestone deposits observed at the upper part along Doma Liji stream.